2019
DOI: 10.1016/j.conbuildmat.2019.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination of GFRC tensile parameters from three-point bending tests using an analytical damage model

Abstract: Glass-fiber-reinforced concrete (GFRC) has been emerging as a widely used construction material that is suitable for many structural elements and particularly flat slabs. This paper presents mix design proportions of GFRC with 0%, 2% and 3% weight fractions of fibers and experimental tests including the 3-point bending tests (NT 21.123 (NF P18-407)) which are usually used in practice. These tests provide indirect information on tensile behavior. They are completed by an identification of the tensile behavior m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Beyond this threshold, there was a noticeable decline in compressive strength. This finding was also noticed by Loukil et al [23] The authors attributed this loss of compression strength to less compaction of the material associated to spaces occupied by the glass fibers.…”
Section: Mechanical Propertiessupporting
confidence: 80%
See 1 more Smart Citation
“…Beyond this threshold, there was a noticeable decline in compressive strength. This finding was also noticed by Loukil et al [23] The authors attributed this loss of compression strength to less compaction of the material associated to spaces occupied by the glass fibers.…”
Section: Mechanical Propertiessupporting
confidence: 80%
“…Glass fibers also exhibit resistance to chemical attack in diverse environments, and from an economic perspective, they may prove more cost-effective than metallic fibers in specific cases. As per Loukil et al [23], the integration of glass fibers within the cementitious matrix emerges as a favorable alternative to steel-reinforced concrete, particularly in the construction of precast electrical equipment shelters and slender structural elements. While autogenous shrinkage is more critical in mass concrete applications, it can influence other types of concrete structures as well.…”
Section: Introductionmentioning
confidence: 84%
“…Results of the current study revealed that GSB had the highest modulus of elasticity mean value followed by GHF then GL with significant differences; this can be attributed to the reduction in the post diameter after surface treatment, which was confirmed by measurements made in the posts after treatment. The reduction of the post diameter is related to the modulus of elasticity since it is calculated by the equation Ef = S4L3/3πd4, which indicated that the modulus of elasticity is inversely proportional to diameter [9], [12], [24], [25].…”
Section: Discussionmentioning
confidence: 99%
“…Posts were loaded to failure in 3-point bending by the ISO standard number 10477 (10.0 mm span, 0.5 mm/min crosshead speed, 2 mm cross-sectional diameter of the loading tip) with a 500 N load cell, using a universal testing machine "Instron universal testing machine model 3354 Instron instruments England." Flexural strength (σ); σ = 8F max L/πd 3 (in MPa) where, F Max is the applied load (in Newton) at the highest point of the loaddeflection curve, L is the span length (6.0 mm), and d is the diameter of the posts (in mm) [3], [6], [12], [15].…”
Section: Three-point Bending Testingmentioning
confidence: 99%
See 1 more Smart Citation